STRATEGIC DIRECTIONS FOR ENSURING STABILITY OF THE FINANCIAL ECOSYSTEM OF UKRAINE - STRILCHUK, Yuliia; LAVRENIUK, Vladyslav; SANDUL, Mariia; LYTVYNENKO, Oleksii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the transformation of Ukraine’s financial ecosystem under the conditions of a full-scale war and identifies the key drivers of its resilience. The study argues that, despite severe economic shocks, infrastructure destruction, and heightened uncertainty, Ukraine’s financial system has demonstrated a remarkable capacity to maintain core functions. This resilience has been ensured through a combination of unconventional monetary and regulatory measures implemented by the National Bank of Ukraine, institutional strength of the banking sector, rapid digitalization of financial services, operational continuity of payment infrastructure, and unprecedented international financial assistance. The paper emphasizes that digital finance and FinTech solutions have played a critical role in preserving access to financial services for households and businesses amid population displacement, power outages, and security risks. The widespread adoption of cashless payments, mobile banking, digital government platforms, and emergency initiatives such as «Power Banking» significantly enhanced the adaptive capacity of the financial ecosystem. At the same time, the study highlights the trade-offs between macrofinancial stabilization and long-term credit expansion, underlining the constraints imposed on investment and reconstruction financing. Special attention is given to Ukraine’s ongoing regulatory convergence with the European Union, including the harmonization of payment systems, financial monitoring standards, and sustainable finance regulations. The integration of ESG principles and the expansion of green and social finance instruments are considered essential components of post-war recovery and long-term competitiveness. Based on the synthesis of empirical evidence and policy analysis, the article systematizes strategic directions for strengthening financial ecosystem resilience in conflict-affected economies. Furthermore, it introduces a conceptual framework for a Financial Ecosystem Resilience Index (FERI), which aggregates macrofinancial, institutional, digital, and behavioral dimensions of resilience. Although the index is not empirically estimated in this study, its formalization and quantitative application are proposed as promising avenues for future research. The Ukrainian case provides valuable insights for policymakers and researchers seeking to design resilient financial systems under conditions of prolonged crisis and uncertainty.